Foresight for digital development (UN New YorkUS, 2016)
Discusses a number of digital development, namely big data, the Internet of things, massive open online courses (MOOCS), three-dimensional printing and digital automation, and their potential long-term effects on the economy, society and the environment.
Keywords: INFORMATION TECHNOLOGY